SPATIAL DISTRIBUTIONS OF NUTRIENTS AND CHLOROPHYLL-A: A POSSIBLE OCCURRENCE OF PHOSPHORUS AS A EUTROPHICATION DETERMINANT OF THE JAKARTA BAY - Hanif Budi Prayitno; . Afdal (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
Phytoplankton blooms due to nutrient enrichment (eutrophication) have been considered as the primary factor causing several massive fish kills occurred in the Jakarta Bay. This study aims to determine the spatial variation of phytoplankton abundance based on chlorophyll-a concentration and its relationship with nutrient level and composition. A field observation was conducted in July 2015 measuring chlorophyll-a and nutrient concentrations. Chlorophyll-a was measured using fluorometer Trilogy AU-10 while nutrients was using spectrophotometer Shimadzu UV-1800. The result showed that chlorophyll-a concentration was relatively higher in the western compared to the eastern region of the Jakarta Bay. In addition, the western region was high in orthophosphate, nitrate and silicate while the eastern region was high in ammonium and nitrate. Statistical analysis shows that chlorophyll-a had the highest significant correlation against orthophosphate in the western region and chlorophyll-a had no significant correlation with nutrients in the eastern region. It seems that phosphorus was the primary determinant of chlorophyll-a variability with a concentration of orthophosphate of more than 0.028 mg P/L is required to increase chlorophyll-a concentration. In addition, low orthophosphate concentration (0.014 mg P/L) below its minimum requirement for maximum phytoplankton growth was likely the factor causing the absence of chlorophyll-a and nutrients relationship in the eastern region. In summary, phosphorus is seemingly the primary eutrophication determinant in the Jakarta Bay.